(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Hepatitis C virus (HCV) infection is a common problem worldwide, affecting millions of people across all populations. In some previous studies, HCV infection was associated with an increased risk of diabetes mellitus or insulin resistance (IR).Insulin Resistance is calculated by Homeostasis Model Assessment (HOMA). Aim: The objective of our study was to evaluate the association between HCV and Insulin Resistance (IR) Setting and Design: A single center, Descriptive case series study which was conducted at Division of Gastroenterology and Hepatology, Medical Unit I, Lahore General Hospital/Post graduate Medical Institute, Lahore. Material and Methods: Total duration of study was about one year conducted from June 2012 to July 2013.HOMAR IR was calculated in all eligible candidates who had detectable HCV RNA PCR level. The cut off value for HOMA IR was taken as 3.8. Statistical Analysis: Was performed using SPSS-release 17, standard version. Results: 300 patients were enrolled and analyzed.154 (51.3%) were female and 146(48.7%) were male and M: F was 1:1.05.Mean BMI was 25.08 kg/m2 .The Mean HOMA IR was 2.62 with S.D 1.76 and S.E. 0.1018. 253(84.33%) patients had HOMA IR <3.7 and 47(15.66%) had HOMA IR 3.8 ≥. No significant Correlation was observed between HOMA IR and BMI. Conclusion: There is significant risk of development of Insulin Resistance in Chronic Hepatitis C infected patients. HCV infection should be taken as systemic disease and Blood glucose level should be regularly monitored in Chronic Hepatitis C patients.